Integration of New Media in Islamic Broadcasting: A Transformative Communication Perspective - Andi Syahputra (Kutubkhanah, 2025)
This study analyzes the integration of new media in Islamic broadcasting from a transformative communication perspective, highlighting changes in interaction patterns and the construction of the meaning of da'wah in the digital space. The research background stems from the increasing use of digital platforms such as YouTube, Instagram, TikTok, podcasts, and artificial intelligence in the dissemination of religious messages, which demands a more participatory communication strategy based on digital literacy. This study uses a qualitative approach based on literature review and analysis of recent scientific articles to examine the dynamics of changes in the digital da'wah ecosystem. The results show that new media create interactive and deliberative two-way communication spaces, as explained in Habermas's theory of interactive communication and public sphere, and has the potential to encourage the transformation of religious awareness in accordance with the concept of transformative communication. However, there is a risk of polarization, commodification of religion, and the spread of misinformation if not accompanied by ethical governance of Islamic broadcasting based on information verification and content moderation. This study recommends the development of an integrative, ethical, and media literacy-based digital da'wah model to strengthen da'wah's function as an instrument of social enlightenment and the formation of a moderate society.